Tripterygium glycosides for safely controlling disease activity in systemic lupus erythematosus: a systematic review with meta-analysis and trial sequential analysis - Yifan Chen; Liuding Wang; Nannan Li; Caiyun Zhou (Frontiers Media S.A., 2023)
Background: Tripterygium glycosides have been used to treat systemic lupus erythematosus (SLE) for a long time, showing the effects of immune regulation. We aimed to evaluate the benefits and risks of Tripterygium Glycosides Tablets (TGT) for patients with SLE.Methods: We searched electronic databases and clinical trial registries for relevant randomized controlled trials (RCTs). We identified eligible RCTs and assessed risk of bias. We conducted a meta-analysis to estimate the pooled effects. The Trial Sequential Analysis (TSA) 0.9.5.10 software was used to verify the reliability of the results.Results: Eight RCTs encompassing 538 patients with SLE were included. TGT combined with conventional treatments (CTs) was superior to CTs alone in reducing lupus activity (MD = −1.66, 95% CI = −2.07 to −1.26, p < 0.00001, low-certainty evidence) and improving overall response rate (ORR) (RR = 1.21, 95% CI = 1.11 to 1.32, p < 0.0001, moderate-certainty evidence). The robustness of the results was confirmed by TSA. Regarding safety, there was no statistical difference in the overall incidence of adverse reactions between the two groups.Conclusion: In patients with SLE, TGT might safely reduce disease activity. However, further high-quality studies are needed to firmly establish the clinical efficacy of TGT.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022300474; Identifier: CRD42022300474.